Автоматизація побудови моделей надійності дубльованої електромеханічної системи з прямим пріоритетом відновлення - Лозинський, О. Ю.; Щербовських, С. В. (Видавництво Львівської політехніки, 2011)
The methods for construction automation of reliability models for doubled system with direct repair priority are suggested. The methods are performed transformation of structure and algorithmic models to discrete-continuous stochastic models of Markov and Monte-Carlo types.
Keywords: надійність; готовність; стратегія відновлення; марковська модель; імітаційна модель